2012
DOI: 10.1016/j.bbadis.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

The importance of ether-phospholipids: A view from the perspective of mouse models

Abstract: Ether-phospholipids represent an important group of phospholipids characterized by an alkyl or an alkenyl bond at the sn-1 position of the glycerol backbone. Plasmalogens are the most abundant form of alkenyl-glycerophospholipids, and their synthesis requires functional peroxisomes. Defects in the biosynthesis of plasmalogens are the biochemical hallmark of the human peroxisomal disorder Rhizomelic Chondrodysplasia Punctata (RCDP), which is characterized by defects in eye, bone and nervous tissue. The generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 106 publications
0
64
0
1
Order By: Relevance
“…For total ePC, there was a significant effect of the brain regions (F (2, 47) ϭ 41.8, PϽ0.01, Fig. 6) and an interaction between injury and the brain regions (F (2,31) ϭ30.6, PϽ0.01). For total ePE, there was a main effect of injury (F (1,38) ϭ5.9, Pϭ0.02), a main effect of brain regions (F (2,30) ϭ4.5, Pϭ0.02) and an interaction between them (F (2,30) ϭ18.1, PϽ0.01).…”
Section: Examination Of Epc and Epe Across Different Brain Regions Inmentioning
confidence: 95%
“…For total ePC, there was a significant effect of the brain regions (F (2, 47) ϭ 41.8, PϽ0.01, Fig. 6) and an interaction between injury and the brain regions (F (2,31) ϭ30.6, PϽ0.01). For total ePE, there was a main effect of injury (F (1,38) ϭ5.9, Pϭ0.02), a main effect of brain regions (F (2,30) ϭ4.5, Pϭ0.02) and an interaction between them (F (2,30) ϭ18.1, PϽ0.01).…”
Section: Examination Of Epc and Epe Across Different Brain Regions Inmentioning
confidence: 95%
“…The usage and characterization of several mouse models helped the understanding of RCDP pathogenesis, the characterization of mechanisms behind the disease, and the assessment of candidate treatments (Braverman et al 2010;Brites et al 2011;da Silva et al 2012). Studies using mouse models for RCDP demonstrated that plasmalogens are fundamental structural phospholipids and protect cells from damage caused by VLCFA accumulation (Brites et al 2009).…”
Section: The Role Of Plasmalogens and Fatty Alcohols In Diseasementioning
confidence: 99%
“…Pex7 -/-mice display similar symptoms to those of patients with rhizomelic chondrodysplasia punctata and only 50 % survive the first 24 hours after birth. Although the exact cause of death has not been established, it has been attributed to the inability to feed due to reduced mobility (32,40). Brites et al reported that the Pex7 -/-mice display extremely reduced plasmalogen levels in almost all analysed tissues, including heart, and exhibit a reduced α-oxidation activity that results in the accumulation of phytanic acid in the plasma (32,40).…”
Section: Frontiers In Cardiovascular Researchmentioning
confidence: 99%
“…Although the exact cause of death has not been established, it has been attributed to the inability to feed due to reduced mobility (32,40). Brites et al reported that the Pex7 -/-mice display extremely reduced plasmalogen levels in almost all analysed tissues, including heart, and exhibit a reduced α-oxidation activity that results in the accumulation of phytanic acid in the plasma (32,40). Braverman et al, who analysed the phenotype of a hypomorphic Pex7 neo/neo mouse, reported a more than 10-fold increase in phytanic acid levels in the heart tissue of animals fed a phytol-containing diet (41,42).…”
Section: Frontiers In Cardiovascular Researchmentioning
confidence: 99%